Congenital anomalies: occurrence and potential risk factors - Pavlović, Ivan; Plećaš, Darko; Plešinac, Snežana; Dotlić, Jelena; Stojanović, Nemanja (Vojnosanitetski pregled, 2021)
Background/Aim. Congenital malformations still represent one of the most important causes of prenatal and infant death. The study aim was to analyze occurrence, outcomes and risk factors of different types of congenital anomalies. Methods. The study included all pregnant women directed to Clinic of Obstetrics and Gynecology, Clinical Center of Serbia, Belgrade due to prenatally diagnosed congenital fetal anomalies during past ten years (January 1, 2008–December 31, 2017). Upon admission to our Clinic a detailed general medical and obstetrical history were taken from every patient. All women underwent genetic testing. Ultrasonography and magnetic resonance were diagnostic methods for fetal malformations confirmation. Results. The study included 773 pregnant women aged from 18 to 46 years. Out of registered nine different groups of fetal anomalies/malformations, the most common were malformations of the central nervous system, while majority of fetuses had combined multiple anomalies. Genetic cause for congenital anomalies was present in 25.2% of pregnancies. Medical pregnancy abortion was performed in 71.8% of cases. Only 10.2% of pregnancies ended in term. The best outcome for children was obtained in case of gastrointestinal anomalies (52% live born). Contrary, only one child with neck and thorax malformations could be saved. According to logistic regression the most important predictor of having a child with combined multiple anomalies was mother’s age, while predictor of central nervous system anomalies was gestational diabetes. The significant predictor of genetic anomalies was mother’s age. Conclusion. In our sample neurological congenital anomalies were the most common, although abnormalities of all organ systems were registered. Majority of pregnancies had to be discontinued due to combined multiple anomalies caused by genetic disorders. Older mother’s age and diabetes can imply on the increased risk for fetal malformations.